2003
DOI: 10.2224/sbp.2003.31.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of the Thin Ideal, Weight and Body Image Concerns

Abstract: Weight and shape concerns in college women are epidemic. Understanding the role of the thin ideal in the development of such concerns is critical for designing prevention programs. This study examines the association between the Sociocultural Attitudes Towards Appearance Questionnaire (SATAQ; Heinberg, Thompson, & Stormer, 1995), a measure of internalization and awareness of the thin ideal, and eating and body image concerns in college women. 70 undergraduates completed questionnaires on eating symptomatology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 18 publications
(27 reference statements)
4
36
0
1
Order By: Relevance
“…Both being overweight and acceptance of attractiveness ideals are related to how women feel about themselves, but interestingly, the two variables are not highly related (Engeln-Maddox 2005). Some overweight women do not endorse cultural standards of thinness and do not feel bad about their appearance (Low et al 2003). Overweight women who internalize thinness ideals may be at particularly high risk of negative outcomes because of the discrepancy between their current appearance and the appearance they think is ideal, as suggested by a recent study of Canadian college women (Sabiston et al 2005).…”
Section: Weight Statusmentioning
confidence: 89%
See 1 more Smart Citation
“…Both being overweight and acceptance of attractiveness ideals are related to how women feel about themselves, but interestingly, the two variables are not highly related (Engeln-Maddox 2005). Some overweight women do not endorse cultural standards of thinness and do not feel bad about their appearance (Low et al 2003). Overweight women who internalize thinness ideals may be at particularly high risk of negative outcomes because of the discrepancy between their current appearance and the appearance they think is ideal, as suggested by a recent study of Canadian college women (Sabiston et al 2005).…”
Section: Weight Statusmentioning
confidence: 89%
“…Numerous studies of American adolescents and college students suggest an association of thin ideal internalization with body dissatisfaction (Engeln-Maddox 2005;Groesz et al 2002;Klaczynski et al 2004), and this relationship is partially explained by comparison processes (Blowers et al 2003). Thin ideal internalization is also related to concerns about eating and weight, particularly among young overweight women in the U.S. (Low et al 2003). Thin ideal internalization is a predictor of disordered eating in young American women (Stice et al 1996;Thompson and Stice 2001), and is believed to be such a critical predictor that some eating disorder prevention programs for college women in the U.S. focus specifically on reducing it (e.g., Stice et al 2001).…”
Section: Thin Ideal Internalizationmentioning
confidence: 99%
“…Only longitudinal research can actually demonstrate whether a factor, such as ethnicity, is protective. In addition, although eating disorder symptomatology concerns in college-aged women are epidemic (Low et al, 2003), the generalization of these findings to other ages and to clinical samples is questionable. Furthermore, we did not use a measure of ethnic identity, which is the degree to which an individual identifies with his or her own ethnic group.…”
Section: Discussionmentioning
confidence: 99%
“…Fingeret, Lee, and Gleaves (2002) found that high levels of self-deceptive enhancement and low levels of past family emphasis on weight control weakened the relationship between awareness and internalization. Low et al (2003) found high body mass index (BMI ¼ kg/m 2 ) strengthened the relationship between internalization and body dissatisfaction. Other factors initially hypothesized as potentially providing protective influences, such as a strong feminist ideology, have produced insignificant or mixed results (e.g., Fingeret & Gleaves, 2004;Twamley & Davis, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Western culture's stereotype of femininity seems to involve the belief that women should be focused upon both taking care of their own appearance and being thin (Worell & Todd, 1996). Women who fail to meet these cultural prescriptions for attractiveness may experience sanctions for being "insufficiently feminine" (Fiske & Stevens, 1993), and internalization of this "thin ideal" has been associated with eating and weight concerns (Low et al, 2003).…”
Section: Studymentioning
confidence: 99%